Dinamika Dakwah Komunitas Te Uti Mongaji - Talalu, Taufik R.; Adam, Sumarlin; Yusuf, Indra Dewi Sery; Nasibu, Sulman A. (UIN Raden Mas Said Surakarta, 2023)
In such a dynamic information era, keeping the younger generation's understanding of religion relevant has become increasingly challenging. This challenge is not only about theoretical understanding of religion, but also about the application of Islamic religious values ​​and teachings in everyday life. This research focuses on the dynamics of the